Strategi Universitas Muhammadiyah Buton dalam Meningkatkan Minat Calon Mahasiswa Baru - Wa Ode Hamiyati Ramadani; Hastuti; Wa Nur Fida (Syntax Idea)
As time progresses, the competition in the higher education sector, both public and private, to attract students is becoming increasingly fierce. They are becoming more aggressive in carrying out specific exercises to compete for the attention of incoming students. With the widening competition among universities, Muhammadiyah Buton University (UM Buton) must play a crucial role in overseeing and disseminating information about the university to the general public. This way, it can increase the interest of potential new students to join and study at the university. In the intense competition in developed countries, universities must continue to compete in providing information to the general public. The exploration technique used in this examination is subjective methodology. Subjective methodology is an exploratory approach that emphasizes understanding and clarification from top to bottom regarding the social uniqueness that occurs, whether related to significance, experiences, or emotional translation of exam participants. The search results indicate that the Advertising methodology of Muhammadiyah Buton University in increasing the interest of potential new students exists in several stages. The idea conveyed is that with the presence of advertising in the hierarchy design of Muhammadiyah Buton University under the overall division leadership, it is hoped that it can transition to other departments, thus making advertising have a reasonable construction.